Squirrel search algorithm for multi-region combined heat and power economic dispatch incorporating renewable energy sources. (1st September 2019) - Basu, M.
Abstract: This paper suggests squirrel search algorithm (SSA) for solving intricate multi-region combined heat and power economic dispatch problem with integration of renewable energy sources. The valve point effect and proscribed workable area of thermal generators and solar and wind power uncertainty have been pondered. SSA is a newly developed swarm intelligence algorithm which emulates the dynamic scavenging activities of squirrels. The efficiency of the suggested method is revealed on a three region test system. Simulation outcomes of the suggested method have been evaluated with those attained by grey wolf optimization (GWO), particle swarm optimization (PSO), differential evolution (DE) and evolutionary programming (EP). It has been examined from the assessment that the suggested SSA has the capability to bestow with better-quality solution. Highlights: SSA is used for solving MRCHPED with integration of renewable energy sources. Valve point effect and proscribed workable area of thermal generators are considered. Solar and wind power uncertainty have been taken into consideration. The efficiency of the suggested method is revealed on a three region test system. Simulation outcomes have been evaluated with those attained by GWO, PSO, DE and EP.